World distribution of Minthea rugicollis (Coleoptera : Lyctidae) - Abood Haris, Faizah; Murphy, Richard J. (Forest Research Institute Malaysia, 2006)
The distribution of Minthea rugicollis worldwide is presented based on a compilation of literature records of population establishments and also from the world collection of M. rugicollis at the Natural History Museum, London. The distribution map derived indicates the limits of distribution for M. rugicollis to be 40° north and south of the Equator, with maximum distribution within 20° north and south. The present compiled records of occurrence of established populations as well as reports on repeated accidental introductions strongly suggest M. rugicollis is not capable of establishing populations under outdoor temperate conditions.